Weight-related stigma is a significant psychosocial stressor in developing countries: Evidence from Guatemala. (July 2016) - Hackman, Joseph; Maupin, Jonathan; Brewis, Alexandra A.
Abstract: Weight-related stigma is established as a major psychosocial stressor and correlate of depression among people living with obesity in high-income countries. Anti-fat beliefs are rapidly globalizing. The goal of the study is to (1) examine how weight-related stigma, enacted as teasing, is evident among women from a lower-income country and (2) test if such weight-related stigma contributes to depressive symptoms. Modeling data for 12, 074 reproductive-age women collected in the 2008–2009 Guatemala National Maternal-Infant Health Survey, we demonstrate that weight-related teasing is (1) experienced by those both underweight and overweight, and (2) a significant psychosocial stressor. Effects are comparable to other factors known to influence women's depressive risk in lower-income countries, such as living in poverty, experiencing food insecurity, or suffering sexual/domestic violence. That women's failure to meet local body norms—whether they are overweight or underweight—serves as such a strong source of psychological distress is particularly concerning in settings like Guatemala where high levels of over- and under-nutrition intersect at the household and community level. Current obesity-centric models of weight-related stigma, developed from studies in high-income countries, fail to recognize that being underweight may create similar forms of psychosocial distress in low-income countries. Highlights: Guatemalan women report teasing related to both underweight and obesity. Effects exceed other known predictors of psychological distress. Models of weight-related stigma focused on obesity need revision in global contexts.